The duality of religious identity in the novel "Demons' Masks" (Journal of the College of Basic Education, 2022)
This research dealt with the issue of the identity crisis and the angles of its formation within the narrative patterns and its diversity and the nature of its cultural background, especially the religious identity. Which is evident in the duality of religious identity in it through the semantic dimension of the religious actions that were implemented by the characters of this novel through the dialectic of invisibility and manifestation. The sacred is a heritage, the paradox is generated through the main character of the novel, which is manifested in the form of sanctity, but the deep structure is completely opposite to the apparent, and it is the actor throughout the vertical line of the narrative discourse, and the circle of contradiction grows with the dominance of negative sexual thought in the novel’s theme, and among these differences embodied in the main character in The novel creates paradoxes and contradictions in the actions of its characters between theory and practice on the one hand, and the connection of this opposing duality to religious thought on the other, meaning that the events of the novel are based on the theme of religious identity, this identity that is supposed to be in one space, but reality put it in another space Completely contrary to the first space, and hostile to it, as the duality of religious identity varied in the elements of the novel at the level of the node, and at the level of (heritage time), and the elements of religious identity witnessed What a creative duality through the duality of its movement along the narrative, and the dual religious identity occupied the narrative construction of the novel from its beginning to its end, as well as its association with the rhetorical image, and the suggestive color, which is an invisible color that we reach through a linguistic value that refers to it.